Dynamics of adaptive and innate immunity in patients treated during primary human immunodeficiency virus infection: results from Maraviroc in HIV Acute Infection (MAIN) randomized clinical trial. (September 2015) - Ripa, M.; Pogliaghi, M.; Chiappetta, S.; Galli, L.; Pensieroso, S.; Cavarelli, M.; Scarlatti, G.; De Biasi, S.; Cossarizza, A.; De Battista, D.; Malnati, M.; Lazzarin, A.; et al.
Abstract: We evaluated the dynamics of innate and adaptive immunity in patients treated with combined antiretroviral therapy (cART) during primary human immunodeficiency virus infection (PHI), enrolled in a prospective randomized trial (MAIN, EUDRACT 2008-007004-29). After 48 weeks of cART, we documented a reduction in activated B cells and CD8 + T cells. Natural killer cell and dendritic cell frequencies were measured and a decrease in CD16 + CD56 dim with a reciprocal rise in CD56 high natural killer cells and an increase in myeloid and plasmacytoid dendritic cells were recorded. In conclusion, 48 weeks of cART during PHI showed significant benefits for both innate and adaptive immunity.